The detection of Mycobacterium avium subsp. paratuberculosis in sheep in the Western Cape, South Africa - Howell, Shannon Kimlynn (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFoodSc)--Stellenbosch University, 2018.